2016
DOI: 10.1177/0954406215612830
|View full text |Cite
|
Sign up to set email alerts
|

Interphase effects on the thermo-mechanical properties of three-phase composites

Abstract: A three-dimensional micromechanics-based analytical model is developed to investigate the influence of interphase on the thermo-mechanical properties of three-phase composites. The representative volume element (RVE) of composites is extended to c × r × h cells in three dimensions and the RVE consists of three phases including filler, matrix and interphase. The arrangement state of filler within the matrix materials is assumed to be random with uniform distribution. Fillers are surrounded by the interphase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Among all others, CNTs have been emerged as the ideal candidates for multifarious applications due to their remarkable thermoelastic and physical properties. The quest for utilizing the remarkable thermomechanical properties of CNTs has led to the emergence of a new area of research that involves the development of nanocomposites . These studies revealed that the addition of a small fraction of CNTs into a polymer matrix introduces significant improvement in the multifunctional properties of microcomposites and nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…Among all others, CNTs have been emerged as the ideal candidates for multifarious applications due to their remarkable thermoelastic and physical properties. The quest for utilizing the remarkable thermomechanical properties of CNTs has led to the emergence of a new area of research that involves the development of nanocomposites . These studies revealed that the addition of a small fraction of CNTs into a polymer matrix introduces significant improvement in the multifunctional properties of microcomposites and nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…One of the main assumptions for deriving the SUC micromechanics model is the perfect bonding condition at the interface between the sub-cells of the RVE. [28][29][30][31] Additionally, it is supposed that the applied normal stress over the RVE does not present any shear stress inside the sub-cells of the RVE. [28][29][30][31] The equilibrium conditions in normal directions between the applied global stresses ( " S l ) (l ¼ x, y or z) over the RVE and local stresses ( ij l ) within each subcell of the RVE are given by…”
Section: Suc Micromechanical Equationsmentioning
confidence: 99%
“…Hassanzadeh-Aghdam et al. 17 developed a three-dimensional micromechanics-based analytical model to explore the influence of interphase on the thermo-mechanical properties of three-phase continuous composites. The results exhibited that the effect of interphase on the thermo-mechanical properties of fibrous composites in the transverse direction is more significant than that of the fiber composites in the longitudinal direction.…”
Section: Introductionmentioning
confidence: 99%